PENGARUH BIAYA OPERASIONAL, BIAYA PRODUKSI, DAN PERPUTARAN PIUTANG TERHADAP LABA BERSIH PADA PERUSAHAAN SEKTOR BARANG KONSUMEN PRIMER - Lifhesti Seroja Khofifah; Rudiyanto; Imas Fatimah (Universitas La Tansa Mashiro, 2024)
The availability of cash is very important in the business world, especially in transactional and operational tasks of a company. This study aims to test and analyze the effect of operating costs calculated using the calculation of production costs plus operational costs, production costs by calculating direct labor costs plus direct material costs plus factory overhead costs, accounts receivable turnover by calculating credit sales. Divided by the average receivables from primary consumer goods sector companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The research method used is a quantitative method using secondary data types, the number of samples used is 41 companies with a total of 164 data selected using purposive sampling technique. Analysis of the data used is multiple linear regression analysis and processed using the SPSS version 20 application. The results of the F test research, namely operational costs, production costs, and accounts receivable turnover on net income simultaneously have a significant effect. The partial test (t test) shows that operating costs have a significant effect on net income, production costs have a significant effect on net income, and accounts receivable turnover has an effect on net income.